Regulierung der nationalen Pharmamärkte in der Europäischen Gemeinschaft - Manfred Erbsland; Angelika Mehnert (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1992)
In this paper we give an overview of government regulations in the national drug markets of the European Community. We describe the admission of new medicines to the market, the organisation of the distribution system, the control of pharmaceutical prices, and the patient copayment schemes for out-of-hospital prescriptions.
Keywords: 330; Arzneimittelmarkt; Regulierung; EU-Staaten